2020
DOI: 10.3390/ani10081277
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Herbal Choline Increases 5-hmC DNA on Whole Blood from Pregnant Ewes and Offspring

Abstract: Herbal formulas during pregnancy have been used in developing countries. Despite that, the potential effects on the mother and offspring and whether those supplements elicit epigenetic modifications is still unknown. Therefore, our objectives were to determine the effects of supplemental herbal choline source (BCho) on the percentage of 5-hmC in whole blood from gestating ewes and their offspring, as well as determining the milk quality and growth of the offspring. Thirty-five gestating Rambouillet ewes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Crosby et al (2017) observed that supplementation of ewes with 4 g/day of herbal choline from 30 days before and until 30 days after the birth increased the lamb's birth weight, the milk production, and the content of oleic fatty acid in the milk. Roque-Jiménez et al (2020) hypothesized that the active compounds of herbal choline have epigenetic properties that could impact the fetal development and growth of the offspring of ewes supplemented during the entire gestation with 4 g/day; however, they only observed increments in milk production, quality of colostrum, and milk. Godinez-Cruz et al (2015) attempted to compare the synthetic and herbal choline in fattening lambs without clear results, since when supplementing with 4 g/kg DM from both sources in sheep they found null effects on the productive response.…”
Section: Herbal Choline In Lambsmentioning
confidence: 99%
“…Crosby et al (2017) observed that supplementation of ewes with 4 g/day of herbal choline from 30 days before and until 30 days after the birth increased the lamb's birth weight, the milk production, and the content of oleic fatty acid in the milk. Roque-Jiménez et al (2020) hypothesized that the active compounds of herbal choline have epigenetic properties that could impact the fetal development and growth of the offspring of ewes supplemented during the entire gestation with 4 g/day; however, they only observed increments in milk production, quality of colostrum, and milk. Godinez-Cruz et al (2015) attempted to compare the synthetic and herbal choline in fattening lambs without clear results, since when supplementing with 4 g/kg DM from both sources in sheep they found null effects on the productive response.…”
Section: Herbal Choline In Lambsmentioning
confidence: 99%
“…The plants Trachyspermum ammi , Citrullus colocynthis , Achyranthes aspera , and Azadirachta indica present the conjugated form of choline—with high concentrations of phosphatidylcholine—and are potential alternative sources to the chloride [ 4 ]. In addition to not having the same undesirable properties as choline chloride, these herbal additives have functional metabolites that benefit animals’ health [ 5 , 6 ]. Furthermore, they can be used in organic foods or in those with a ‘natural’ advertising appeal [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, alternative sources of feedstuff should be evaluated to maximize animal production [ 18 , 19 ]. Recently, research that focused on using herbal feed additives has reported beneficial effects on livestock [ 20 ]. Herbal feed additives have been reported with different bioactive compounds, such as alkaloids, polyphenols, isothiocyanates, tannins, saponins, and terpenoids, all of which can stimulate the immune system [ 21 ].…”
Section: Introductionmentioning
confidence: 99%